Initiation Model of Sustainable Human Resource Management Through Knowledge Sharing and Job Satisfaction - Awanis Linati Haziroh; Febrianur Ibnu Fitroh Sukono Putra; Ririt Iriani Sri Setiawati; Mochammad Eric Suryakencana Wibowo (Journal of Economics, Business, and Government Challenges, 2022)
Initiation Model of Sustainable Human Resource Management Through Knowledge Sharing and Job Satisfaction